Long-term outcomes of third-line therapy with tyrosine kinase inhibitors in chronic phase chronic myeloid leukemia: A real-life experience - Chitanava, Tamara; Matvienko, Iuliia; Shuvaev, Vasily; Voloshin, Sergey; Martynkevich, Irina; Vlasova, Yulia; Efremova, Elizaveta; Mileeva, Ekaterina; Pirkhalo, Anna; Makarova, Taiana; Vlasik, Roman; Karyagina, Elena; et al. (Frontiers in Oncology, 2023)
Tyrosine kinase inhibitor(TKI) therapy has greatly improved the prognosis of patients with chronic myeloid leukemia(CML), improving the survival expectancy of patients with chronic-phase(CP)CML to that of the general population. However, despite these advances, nearly 50% of patients with CMLCP experience failure to respond to frontline therapy, and most fail to respond to the subsequent second-line TKI. Treatment guidelines for patients failing 2nd line therapy are lacking. This study aimed to determine the efficacy of TKIs as third-line therapy in a “real-world” clinical practice setting and identify factors favorably influencing the long-term outcomes of therapy. We have retrospectively analyzed the medical records of 100 patients with CP CML. The median age of patients was 51(range, 21–88)years, and36% of patients were male. The median duration of the third-line TKI therapy was22(range, 1–147)months. Overall, the rate of achieving complete cytogenetic response (CCyR)was 35%. Among the four patient groups with different levels of responses at baseline, the best results were achieved in the groups with any CyR at the baseline of third-line therapy. Thus,СCyR was reached in all15 and8/16 (50%) patients with partial cytogenetic response(PCyR) or minimal or minor CyR(mmCyR), respectively, whereas CCyR was detected only in12/69(17%) patients without any CyR at baseline(p<0.001). Univariate regression analysis revealed that the factors negatively associated with CCyR achievement in third-line TKI therapy were the absence of any CyR on first- or second-line TKI therapy(p<0.001),absence of CHR prior to third-line TKI(p=0.003) and absence of any CyR prior to third-line TKI(p <0.001). During the median observation time from treatment initiation to the last visit(56[4–180]months), 27% of cases progressed into accelerated-phase or blast-phase CML, and32% of patients died. Progression-free(PFS) and overall survival(OS) were significantly higher in patients with CCyR on third-line than the group without CCyR on third-line therapy. At the last visit, third-line TKI therapy was ongoing in18% of patients, with a median time of treatment exposure of58(range, 6–140) months; 83% of these patients had stable and durable CCyR, suggesting that patients without CHR at baseline and without CCyR at least by12 months on third-line TKI should be candidates for allogeneic stem cell transplantation, third-generation TKIs, or experimental therapies.